The crisis in legally aided criminal defence in Wales: bringing Wales into discussions of England and Wales. (June 2021) - Dehaghani, Roxanna; Newman, Daniel
Abstract: This paper explores the impact of cuts and continued fee stagnation on publicly funded criminal defence in England and Wales. In so doing, we take an explicit focus on Wales, which has been neglected in socio-legal scholarship on criminal justice matters. Drawing on 20 interviews with criminal defence lawyers in south Wales, we examine how they have experienced the changes to criminal legal aid in recent years. The lawyers in this study largely considered underfunding as a key political issue, with criminal legal aid identified as an easy target, also highlighting concerns around the impact of underfunding on their practice and how they can work for clients. As such, lawyers queried whether there is a viable future for criminal legal aid. These findings have implications for Wales, and the whole England and Wales jurisdiction, as we will discuss throughout.